Aggressive scalp and sternal lesion: a presentation of rare case of metastatic eccrine carcinoma - Cha Sha Rownose; Mohamad Sobri Mohamad Saupi; Siti Zubaidah Sharif; Nik Amin Sahid Nik Lah (Elsevier Ltd, 2021)
Introduction: Ductal Eccrine carcinoma (DEC) is a rare primary cutaneous tumor that exhibits both squamous and adnexal ductal differentiation. Due to its rarity in clinical practice we present as case of DEC and a literature review on the latest management of this rare disease. Case presentation: We report a case 41 years old female presented with lesion on the scalp and sternal mass, increasing in size with itchiness and erythematous for 6 months duration. Further CECT scan of brain and neck shows features of malignant left frontal scalp lesion with poor plane with overlying skin and underlying skull bone and CECT of thorax shows a large, irregular heterogeneously enhancing mass with necrotic center noted at right hilar within superior segment of right lower lobe, encasing right middle and lower lobe bronchi. Wedge biopsy of scalp lesion showed an intradermal lesion extensively infiltrating by malignant gland accompanied by desmoplasia and the tumor cells are seen extending into the surgical margins suggestive of ductal eccrine carcinoma. Clinical Discussion:This case highlights the importance and challenges in achieving early diagnosis coupled with the scarcity of information on these leads to difficulty in managing this patient. Conclusion: In managing Ductal Eccrine Carcinoma tumor, standard method of treatment for has not been established. However, wide surgical excision is the treatment of choice for localized lesions. Regarding prognosis, there is conflicting data published which we describe in this article.